Compulsion, compliance, and competitiveness: Indonesia’s mandatory halal regime and the ambition to lead the global halal economy - Mochamad Dandi (PRIVIETLAB, 2026)
Indonesia has made a distinctive wager on the global Halal economy. Under Law No. 33 of 2014 on Halal Product Assurance, halal certification has shifted from a voluntary market signal to a legal obligation, which will be phased in for food and beverage products starting October 2024. The certifying authority or Badan Penyelenggara Jaminan Produk Halal (BPJPH) has been elevated to a non-ministerial body that reports directly to the President (Indonesia Satu, 2025). Officials now describe Indonesia as the only country operating “full sharia compliance” in food and beverages and report that the halal value chain contributes roughly 27% of the gross domestic product and grows faster than the wider economy (Bank Indonesia, 2026). Against the government’s stated ambition to move from third to first on the Global Islamic Economy Indicator (DinarStandard, 2024), this commentary asks whether legal compulsion can build genuine competitiveness in the halal industry. Drawing on Scopus- and Web of Science–indexed scholarship, this study argues that mandatory certification has delivered scale and a strong domestic value chain but risks an administrative burden that falls hardest on micro-enterprises, a governance bottleneck at the certifying authority, and a form-over-substance trap in which certification is mistaken for quality. It contends that competitiveness requires traceability, integration with Islamic finance, proportionate treatment of small enterprises, and mutual recognition of exports.